Treasure hunters [compact disc, unabridged] - Patterson, James, 1947- (Patterson, James, 1947- Treasure hunters, 2013)
"Bick Kidd's parents were world-famous treasure hunters--until they mysteriously disappeared. Now he and the rest of the Kidds--Beck, Tommy, and Storm--have to finish their mom and dad's last major mission-- before it finishes them"--Container.